Impact of water quality on concrete mix and hardened concrete parameters - Kokoszka, Wanda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the present article is the evaluation of the use of different water types in the production of concrete mix and C20/25 class concrete (assuming the same composition). Taking as an example a selected Subcarpathia-based concrete production plant, equipped with a process water management system, the research analysed the quantity-quality parameters of drinking water, sewage water, and groundwater and evaluated them for their accordance with mixing-water quality standards.
Keywords: concrete compressive strength; mixing water; ready-mixed concrete; sewage water; wytrzymałość betonu na ściskanie; mieszanie wody; beton towarowy; woda ściekowa